1989
DOI: 10.1143/jjap.28.l1236
|View full text |Cite
|
Sign up to set email alerts
|

InGaAsP/InP Lasers with Two Reactive-Ion-Etched Mirror Facets

Abstract: Reactive ion etching in chlorine, methane, argon and hydrogen was used to etch smooth vertical mirror facets on both sides of InGaAsP/InP lasers. Optical measurements and lifetests show these lasers to have the same characteristics as lasers with cleaved facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The removal rate of this product and therefore the etch rate of In-containing compounds has been shown to be highly dependent on temperature [4,5] and/or additive gases such as Ar and N 2 [6][7][8][9][10][11]. At temperatures above 150 • C there is a significant increase in etch rate due to thermally-assisted desorption of InCl 3 and in reactive ion etching (RIE) systems with Cl 2 or BCl 3 chemistries it has been necessary to use sample temperatures >150 • C while etching [12,13]. In RIE and electron cyclotron resonance (ECR) systems significant increases in room temperature etch rate of In-containing materials by the addition of neutral additive gases have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The removal rate of this product and therefore the etch rate of In-containing compounds has been shown to be highly dependent on temperature [4,5] and/or additive gases such as Ar and N 2 [6][7][8][9][10][11]. At temperatures above 150 • C there is a significant increase in etch rate due to thermally-assisted desorption of InCl 3 and in reactive ion etching (RIE) systems with Cl 2 or BCl 3 chemistries it has been necessary to use sample temperatures >150 • C while etching [12,13]. In RIE and electron cyclotron resonance (ECR) systems significant increases in room temperature etch rate of In-containing materials by the addition of neutral additive gases have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is generally found that a non-volatile etch product (InCl 3 ) rapidly forms a thick selvedge layer that leads to low etch rates and rough non-stoichiometric surfaces. In reactive ion etching (RIE) it is necessary to heat samples to ∼ 150 • C in order to promote desorption of the InCl 3 [15,16]. Recent work has shown that sample heating to this temperature is not necessary if very high ion densities can be produced, for example by microwave enhancement of the plasma [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%